Sustainability in interior design - Moxon, Siân (Portfolio skills. Interior design., 2012)
The environmental impact of interior architecture and design practice is immense, and this book highlights the need for designers to adapt the way they work and relearn the lessons lost in order to make their designs fully sustainable. Contrary to many preconceptions, sustainable design can be sophisticated and stylish. By its nature, a sustainable approach means considering the whole life cycle of a project, thereby improving the functionality, quality, and human enjoyment and, in the long term, bringing real social and economic benefits. This book is filled with examples and techniques, together with historical and contemporary case studies, all supported by invaluable resources and links. A comprehensive reference book for anyone wanting to work in interior design, this book introduces ideas of sustainability while encouraging and inspiring readers with positive, creative, and practical alternatives.